2014
DOI: 10.1371/journal.pone.0114214
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of Oxidized LDL in the Tendon Tissues of C57BL/6 or Apolipoprotein E Knock-Out Mice That Consume a High Fat Diet: Potential Impact on Tendon Health

Abstract: ObjectiveClinical studies have suggested an association between dyslipidemia and tendon injuries or chronic tendon pain; the mechanisms underlying this association are not yet known. The objectives of this study were (1) to evaluate the impact of a high fat diet on the function of load-bearing tendons and on the distribution in tendons of oxidized low density lipoprotein (oxLDL), and (2) to examine the effect of oxLDL on tendon fibroblast proliferation and gene expression.MethodsGene expression (Mmp2, Tgfb1, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Previous data reported detrimental effects of HF diet on tendon biomechanical and morphological properties (Boivin et al, 2013;Grewal et al, 2014). Diet switch from HF diet to lowfat diet seems to resolve metabolic dysfunction, but it was not able to reverse tendinopathic changes (Studentsova et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous data reported detrimental effects of HF diet on tendon biomechanical and morphological properties (Boivin et al, 2013;Grewal et al, 2014). Diet switch from HF diet to lowfat diet seems to resolve metabolic dysfunction, but it was not able to reverse tendinopathic changes (Studentsova et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In animal models, consumption of high-fat (HF) diet promotes deleterious effects on morphological, biomechanical and biochemical properties of tendons (Biancalana et al, 2010;Boivin et al, 2013). Previous data have shown that rats exposed to HF diet displayed an increase of oxidized lowdensity lipoprotein deposition in extracellular matrix (ECM) as well a reduction of failure stress in the patellar tendon when compared with rats exposed to a standard diet (Grewal et al, 2014). Zucker rats displayed disorganized collagen fibril bundles and decreased average fibril diameter accompanied by adverse effects in displacement at maximum load and maximum strain, indicating a significant harmful ECM remodeling in deep digital flexor tendon (Biancalana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Apolipoprotein E is required for normal catabolism and clearance of lipoprotein constituents and acts as a ligand for cell-surface LDL receptors. Therefore, apoE-knockout mice (apoE (−/−) ) experience a severe, progressive form of hypercholesterolemia, making them the most commonly employed model for studying the adverse influence of cholesterol on various body [ 30 ]. NAFLD, affecting up to a third of the population in many developed countries [ 31 ], has recently attracted considerable attention worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a study on mice to examine the influences of localised lipid (within or around the tendon tissue) versus systemic lipid (hypercholesterolaemia) on tendon biomechanical properties. 48 Two strains of mice (normal mice or mice predisposed to developing hypercholesterolaemia, the apolipoprotein E knockout (ApoE-KO) model) were fed a normal diet, or a high-fat diet. Interestingly, the accumulation of adipose tissue around tendons occurred in normal mice that were fed a high-fat diet, and their tendons demonstrated a significant reduction in failure load and stress compared with mice on a normal diet.…”
Section: Integrated Model—the Systemic Influence Of Lipid On Tendons mentioning
confidence: 99%